Quantitative Mid‐Infrared Plasmonic Biosensing on Scalable Graphene Nanostructures. Issue 2 (27th November 2022) - Bareza, Nestor Jr.; Wajs, Ewelina; Paulillo, Bruno; Tullila, Antti; Jaatinen, Hannakaisa; Milani, Roberto; Dore, Camilla; Mihi, Agustin; Nevanen, Tarja K.; Pruneri, Valerio
Abstract: Graphene nanostructures, exhibiting tunable and nanoscale‐confined mid‐infrared (mid‐IR) plasmons, prevail as a powerful spectroscopic platform for novel surface‐enhanced molecular identification. Particularly, graphene shows exciting opportunities for biosensing applications due to its versatile functionalization methods with different biomolecular building blocks (e.g., enzymes, proteins, and DNA). Here, a quantitative bioassay based on the mid‐IR localized surface plasmon resonance (LSPR) modulation in functionalized graphene nanostructures is demonstrated. Specifically, vitamin B12 (vB12 ) using the specific recognition elements on modified graphene nanoribbons (i.e., pyrene linkers via π − π stacking + anti‐vB12 antibody fragments via amide bond) is detected. Different concentrations of vB12 spotted on an arrayed panel of a single chip are quantified by the graphene LSPR shifts, where a limit of detection (LOD) of 53.5 ng mL −1 is obtained. The upscaling potential of the bioassay using large area nanostructured graphene films produced by nanoimprinting 2D hole arrays is illustrated. The integration of quantitative bioassay with scalable graphene nanostructures shows promising routes of graphene‐based mid‐IR platforms toward prospective industrial applications. Abstract : An array of graphene nanoribbons is used for a direct, label‐free detection of small biomolecules, such as vitamin B12 . The optical detection is done by using the mid‐IR LSPR method. The obtained 53.5 ng mL −1 LOD and proven use of the same bioassay on a large‐area nanoimprinted graphene nanoholes show very promising routes of graphene‐based mid‐IR platforms toward commercial applications.